2003
DOI: 10.1046/j.1526-4610.2003.03062_23.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence of altered skeletal muscle blood flow in chronic tension‐type headache.

Abstract: Brain. 2002 Feb;125(Pt 2):320‐326 Painful impulses from tender pericranial muscles may play a major role in the pathophysiology of chronic tension‐type headache. Firm evidence for peripheral muscle pathology as a cause of muscle pain and chronic headache is still lacking. Using a microdialysis technique, we aimed to estimate in vivo blood flow and interstitial lactate concentrations in the trapezius muscle at rest and during static exercise in patients with chronic tension‐type headache and in healthy subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 0 publications
7
41
0
1
Order By: Relevance
“…In two studies of one group of patients (Ashina et al, 2002;Ashina et al, 2003) with chronic tension headaches, no differences were found in metabolites and some algesic substances (e.g., BKN and PGE2) in the trapezius muscle ( Table 5). …”
Section: Chronic Tension Type Headachesmentioning
confidence: 96%
“…In two studies of one group of patients (Ashina et al, 2002;Ashina et al, 2003) with chronic tension headaches, no differences were found in metabolites and some algesic substances (e.g., BKN and PGE2) in the trapezius muscle ( Table 5). …”
Section: Chronic Tension Type Headachesmentioning
confidence: 96%
“…Some have studied this as outside of headache and found that muscle tenderness and EMG activity levels were significantly increased compared to values in controls subjects. It is concluded that one of the primary sources of pain in tension-type headache may be a local and reversible sensitization of nociceptors in the pericranial muscle, mechanical strain [14], and muscle ischemia [15]. Previous reports showed altered blood flow in muscle was caused by disturbed regulation of peripheral mechanisms because of central sensitization or generalized hyperalgesia [16].…”
Section: Mattoo Et Almentioning
confidence: 99%
“…The link from exercise to venous occlusion appears to exist in some reports. 15,33) But there are contrary reports, 34) so this link may depend on muscle and method. The link from venous occlusion to pain requires exercise 35,36) and perhaps complete occlusion.…”
Section: Endurance Timesmentioning
confidence: 96%